Histomorphometric evaluation of a threaded, sandblasted, acid-etched implant retrieved from a human lower jaw: A case report - Sakakura, Celso Eduardo [UNESP]; Nociti Jr., Francisco Humberto; Mello, Guilherme Paulo Scarpel; De Mello, Elaine Duarte Artuso; De Rezende, Maria Lúcia Rubo (Wolters Kluwer, 2005)
The purpose of this study was to histomorphometrically evaluate the bone-to-implant contact and bone area around a titanium implant retrieved from a human lower jaw. A screw-shaped titanium implant (sandblasted and acid-etched surface) was removed from a 68-year-old male after having been in function for 40 months because of a fracture of the abutment screw. Following the implant removal, an undecalcified section was obtained. The histomorphometric analysis showed a rate of 75.40% of bone-to-implant contact and 89.30% of bone area filling within the limits of the implant threads. The surrounding bone healed in a well-organized pattern and could not be differentiated from the anginal alveolus. The histologic evidence showed a high degree of osseointegration in a threaded, sandblasted, and acid-etched implant retrieved from a human lower jaw after functional loading for 40 months. Copyright © 2005 by Lippincott Williams & Wilkins.
Keywords: Abutment screw fracture; Dental implants; Osseointegration; Overload; Porous surface; titanium; aged; bone development; bone regeneration; case report; chemistry; dental acid etching; dental surgery; denture; human; jaw; male; mandible; pathology; physiology; surface property; tooth implantation; tooth prosthesis; wound healing; Acid Etching, Dental; Aged; Air Abrasion, Dental; Alveolar Process; Dental Abutments; Dental Implants; Dental Prosthesis Design; Dental Restoration Failure; Humans; Male; Mandible; Osteogenesis; Surface Properties; Titanium; Wound Healing